Komunikasi Antarbudaya: Akulturasi Bahasa dalam Masyarakat Pendalungan Kabupaten Jember - Putri Efendi, Yunia Permadani; Cahyono, Hery B. (MEDIAKOM : Jurnal Ilmu Komunikasi, 2019)
This study aims to determine the acculturation of inter-ethnic Javanese language and ethnic Madurese in Jember regency. This study uses qualitative research methods in descriptive form. The author raises the theme of acculturation Pendalungan culture is based on observations in the community of Pendalungan Jember which uses two languages at once when communicating. This uniqueness is the attraction of this new culture to be studied. Javanese culture and Madurese culture that merge into one and form a new culture gives color to cultural diversity in Indonesia. This unique Pendalungan dialect is only found in Jember Regency. The problem in this research is how the acculturation of Javanese language and Madurese language in Pendalungan culture, Factors that influence the occurrence of acculturation of Javanese and Madurese languages in Pendalungan culture, obstacles to the acculturation of Javanese and Madurese languages in Pendalungan culture. The results of this study indicate that the acculturation of Javanese and Madurese languages occurs due to migration of residents from other regions to Jember Regency. The cause of the acculturation of Javanese and Madurese languages in Jember is due to historical factors, social and economic contacts. Some obstacles to the acculturation of Javanese and Madurese languages in Jember are ethnocentric, native cultural backgrounds, and languages